Peluang Dan Tantangan Integrasi Nilai-Nilai Hukum Islam Dalam Sistem Hukum Nasional - Ratni Kasmad (IAIN Palopo, 2021)
The existence of Islamic law in Indonesia has a long history, starting from the time of the Islamic empire, where the law lives in a society with the Sultan (King) as the highest power holder who gave birth to the theory of creed or creeds among observers of Islamic law. Then the Dutch colonial period that came to Indonesia began to narrow the space and the development of Islamic law, but Muslims still fight for and maintain the Islamic law until Indonesia's independence. After that the old order where the position of Islamic law is still relatively weak and has no significant change even though at that time has been present Act no. 1 the Year 1974 concerning marriage, Law no. 7 of the 1989 Religious Courts and KHI. Then the new order whose presence was a fresh breeze that gave new spirit and hope for the development of Islamic law but the result was disappointing because the government of that time showed its power. After that emerged a period of reform that is so evolving and progress in society until now, it can be seen by the enactment of some legislation from the values of Islamic law in the national legal system. In such changes, the opportunities and challenges of Islamic law in the national legal system must always experience ups and downs so it needs to be investigated further. This study describes and analyzes the challenges and opportunities of integration of Islamic law in the national legal system. This research uses the Library research method, with the procedure of reduction, presentation, and data analysis. The results show that Islamic law has an opportunity to provide input for the formation of national law because one of them is the majority of Indonesia's population is Muslim. The challenges can be seen structurally, substantially, and culturally.